2016
DOI: 10.1161/hypertensionaha.116.07088
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin 1–7 Is a Negative Modulator of Aldosterone Secretion In Vitro and In Vivo

Abstract: Angiotensin 1-7 and Aldosterone 379Adrenocorticotropic hormone (ACTH, synacthene 0.25 mg/mL) was purchased from Sigma-tau. The Ang 1-7 receptor (Mas1) antagonist A779 was purchased from Bachem-Israel (product number H-2888.0025). Low-salt rat chow was purchased from Harlan laboratories (Tekland 7034, 0.1% sodium).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…In fact a number of noncanonical mechanisms of angiotensin pathways represent possible novel upstream targets to inhibit aldosterone/mineralocorticoid receptor-dependent pathways, for example, the ACE2/Ang-(1-7) pathway and their novel regulatory elements such as sheddases (ADAM 17) or apelin (which increases ACE2 promotor activity) [129], as well as Ang-(1-12)/chymase/Ang II pathway. As expected, interventions blocking Ang-(1-12)/chymase/Ang II as well as enhancing ACE2/Ang-(1-7) diminished aldosterone production [124,130]. It remains to be determined, however, which of the novel pharmacotherapies, shown to be effective in experimental heart failure including chymase inhibitors [131], recombinant human ACE2 [132][133][134], Ang-(1-7) [135], or combined angiotensin receptor antagonist and neprilysin inhibitor (ARNI) [104], are most effective in reducing the activity of aldosterone/mineralocorticoid receptor-dependent signaling.…”
Section: Resultssupporting
confidence: 72%
“…In fact a number of noncanonical mechanisms of angiotensin pathways represent possible novel upstream targets to inhibit aldosterone/mineralocorticoid receptor-dependent pathways, for example, the ACE2/Ang-(1-7) pathway and their novel regulatory elements such as sheddases (ADAM 17) or apelin (which increases ACE2 promotor activity) [129], as well as Ang-(1-12)/chymase/Ang II pathway. As expected, interventions blocking Ang-(1-12)/chymase/Ang II as well as enhancing ACE2/Ang-(1-7) diminished aldosterone production [124,130]. It remains to be determined, however, which of the novel pharmacotherapies, shown to be effective in experimental heart failure including chymase inhibitors [131], recombinant human ACE2 [132][133][134], Ang-(1-7) [135], or combined angiotensin receptor antagonist and neprilysin inhibitor (ARNI) [104], are most effective in reducing the activity of aldosterone/mineralocorticoid receptor-dependent signaling.…”
Section: Resultssupporting
confidence: 72%
“…Indeed, Kawrazaki et al 35 demonstrated that aldosterone receptor activation and HSD intake induce inflammation and oxidative stress. In young (3-week-old) and adult (10-week-old) uninephrectomized Sprague-Dawley rats fed with a HSD, the aldosterone-induced organ damage was attenuated with eplerenone (aldosterone receptor antagonist), olmesartan (AT 1 R antagonist), and FAD286 (aldosterone synthase inhibitor) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that severe hypertension and organ injury in young rats after HSD intake was primarily due to aldosterone receptor activation and secondarily to AT 1 R activation. 35 Figure 1 summarizes the course of activation of the two main arms of RAAS: ACE/Ang II/AT 1 R and ACE2/Ang-(1-7)/MAS in tissue. We highlighted in this figure the ACE/ACE2 ratio determining the fate of the system during HSD intake and the AT 1 R responses as the end point of the inappropriate RAAS activation.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that the levels of angiotensinogen, Ang II, and mineralocorticoids are increased in pregnancy and lead to preeclampsia [ 11 , 24 ]. Further, to regulate this increased blood pressure, a compensatory increase in ACE 2 activity leads to the production of Ang (1–7) which causes vasodilation, reduces the production of aldosterone by acting on adrenal glomerulosa cells [ 23 , [25] , [26] , [27] , [28] ]. ACE 2 has an antihypertrophic activity that plays a pivotal role in cardiac tissue during the gestational period and may modulate myocardial tissue growth [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%